Training And Resistance to Change: Work with a Group of Prison Guards. Issue 6 (18th August 2018) - Gozzoli, Caterina; D'Angelo, Chiara; Tamanza, Giancarlo
Abstract : Change has always been a delicate and complex process for people, groups, and organizations that experience it. This work, starting with a reorganization process that involved a Lombard penitentiary, analyzes resistance to change in a group of 15 supervisors and their evolution throughout a training program in which they participated. The purpose of this study is to carry out an exploratory investigation of the role of the group in training, as an instrument capable of accompanying and helping to evolve resistance to change. In order to understand whether and how the temporary micro-organization created during the training was able to help the subjects to deal with emerging defenses triggered by the change process, an analysis was done of the written content of the transcripts of seven training sessions. The analysis made it possible to highlight some types of resistance in the group like shifting the problems, individual understandings of the problems, the preponderance of complaints, and the messianic expectation of a management figure deciding how to intervene. The evolution of the training program, through specific activities and actions implemented by the instructor, allowed the group to make a progressive step toward freeing the project mindset and a more active and proactive attitude. The resistance was welcomed and supported, providing a way for emotions (frustration, anger, tiredness, etc.) to be expressed in words and to be released and then leave space for a new group project mindset.